The Influence Of Social Media Marketing And Electronic Word Of Mouth (E-Wom) On Purchase Intention (Survey on Netflix application consumers in Tasikmalaya City) - Nurazizah, Tasha Shafa; Pauzy, Depy Muhamad; Arif (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effect of social media marketing and electronic word of mouth on consumer buying interest in Netflix Tasikmalaya City. The method used is a quantitative descriptive approach. A total of 100 respondents were taken as samples using non-probability sampling techniques from the population of all downloaders of the Netflix application in Tasikmalaya City. This study uses path analysis with SPSS version 26 as the test tool. The results obtained in this study that social media marketing has a significant effect on purchase intention, electronic word of mouth has a significant effect on purchase intention, social media marketing has a significant effect on purchase intention through electronic word of mouth.